Insights From Library Information and Resource Sharing for the Future of Academic Library Collections. Issue 2 (3rd July 2019) - Posner, Beth
Abstract: The successes and challenges of library resource sharing offer important lessons for librarians considering the future of academic library collections. Library resource sharing specialists provide interlibrary loan services because neither the Internet, nor any one library, holds all of the information that people need. And, how well ILL departments can facilitate access to information, in traditional and innovative ways, depends on many factors, including copyright guidelines, license terms, publisher embargoes, high publisher paywalls for article access, the existence of both legal and illegal social sharing, and, especially, on what librarians continue to collect, maintain and preserve.